Rapport au savoir en EPS à l’école primaire - Marie-Paule Poggi; Mathilde Musard (Recherches en Éducation)
This study focuses on the meaning that students give to their learning experience in physical education (PE) in primary school, ie in relation to knowledge they develop. The aim is to better understand the sense the students give to the learning settings and to identify which registers of activities they mobilize to succeed and learn in PE. Sixty-five students from 10 different classes (from CE1 to CM2), stemming from two sociologically contrasted schools, were questioned in the form of interviews during the lesson. The results show that the report to learn it manufactures both in duration, repetition, based on internalized habits, but also in interactions with teachers, peers, or even outside of school (family, club ...). It therefore seems fruitful to cross the individual and the social, the subject’s past and present interactions, inside and outside the classroom to better understand the relationship to knowledge of students in PE.